Pengaruh Macam Pupuk Organik Terhadap Pertumbuhan dan Hasil Jagung Manis (Zea mays-saccharata, Start) - Sukuriyati Susilo Dewi; Bambang Heri Isnawan; Dwi Purwana (Universitas Muhammadiyah Yogyakarta, 2005)
A field research to observe the effect of kinds of organic manure and on growth and yield of sweet corn was done in Danguran village, Klaten Regency of Midle Java. The research was conducted during August to October 2003. The field experiment was arranged in a Randomized Complete Block Design, with 3 replications. The kinds of organic manure treatment consisted of 5 levels which are: no farm manure (PKO), chicken farm manure (PKl), vermicompost or Kascing (PK2), cow farm manure A (PK3), and cow farm manure-B (PK4). Each organic matter given was 10 ton /ha. The result showed that the chicken farm manure gave the significantly higher growth and yield of sweet corn than the others. The average sweet corn yield obtained in this research was 16,2 ton/ha.